2018
DOI: 10.1108/ijefm-01-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the perceived value of festival experiences: the case ofSerralves em Festa!

Abstract: Purpose Serralves em Festa! is a festival of contemporary artistic expression held annually in the city of Porto attracting a large number of national and international tourists. As there is no entrance fee, the purpose of this paper is to examine the effect of the perceived value through the attendee’s willingness to pay for the event. The authors also describe the respondents (the “cheap talkers”) who indicated that they are willing to pay for a festival but when compared to other groups their opinion is dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…Knowing that nowadays consumers are especially aware of this type of issues, these are strategic factors to know these trends and also analyse the impacts that this sort of actions carried out by cultural agents cause on visitors. These findings reinforce the proposals by Cagut et al [48], regarding the relationship between sustainability and consumer behaviour, and also the relationship between satisfaction with the visitor experience and the intention to return in the future, identified by [46]. This work presents some limitations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Knowing that nowadays consumers are especially aware of this type of issues, these are strategic factors to know these trends and also analyse the impacts that this sort of actions carried out by cultural agents cause on visitors. These findings reinforce the proposals by Cagut et al [48], regarding the relationship between sustainability and consumer behaviour, and also the relationship between satisfaction with the visitor experience and the intention to return in the future, identified by [46]. This work presents some limitations.…”
Section: Discussionsupporting
confidence: 87%
“…This entire environment is also recognized as a national monument, and it is there that the cultural event that is our object of study takes place. Considered as the largest contemporary cultural event in Europe, it presents proposals for 40 consecutive hours, in a free access format to the contemporary art museum, the foundation's heritage and the park, where installations, interventions and artistic performances take place [46]. The constant increase in visitor numbers is also linked to the affirmation of the city of Porto as a tourist destination of excellence.…”
Section: Data Methods and Resultsmentioning
confidence: 99%
“…Most research in hospitality to date has focussed on the experiential dimensions of services and events such as participants’ motivations of attending music festivals (Szmigin et al , 2017), value co-creation practices and outcomes (Camilleri and Neuhofer, 2017; Rihova et al , 2018), while wider social, emotional and behavioural benefits are often overlooked (Borges et al , 2018; Mair and Weber, 2019). What is a significant gap in research is the need to go beyond hedonistic experiences and tap into the realm of transformational value.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [66] evaluated the festival experience of the Serralves Fiesta using the CVM. The results showed that females and people over 53 years of age are more willing to pay for the festival.…”
Section: The Application Of Cvm To Festivalsmentioning
confidence: 99%